CRISPR/Cas9 Ribonucleoprotein-Based Genome Editing Methodology in the Marine Protozoan Parasite Perkinsus marinus - Yadavalli, Raghavendra; Umeda, Kousuke; Waugh, Hannah A.; Tracy, Adrienne N.; Sidhu, Asha V.; Hernández, Derek E.; Fernández Robledo, José A. (Frontiers in Bioengineering and Biotechnology, 2021)
Perkinsus marinus (Perkinsozoa), a close relative of apicomplexans, is an osmotrophic facultative intracellular marine protozoan parasite responsible for ‘Dermo’ disease in oysters and clams. Although there is no clinical evidence of this parasite infecting humans, HLA-DR40 transgenic mice studies strongly suggest the parasite as a natural adjuvant in oral vaccines. P. marinus is being developed as a heterologous gene expression platform for pathogens of medical and veterinary relevance and a novel platform for delivering vaccines. We previously reported the transient expression of two rodent malaria genes Plasmodium berghei HAP2 and MSP8. In this study, we optimized the original electroporation-based protocol to establish a stable heterologous expression method. Using 20 µg of pPmMOE[MOE1]: GFP and 25.0 x106 P. marinus cells resulted in 98% GFP positive cells. Further, using the optimized protocol, we report for the first time the successful knock-in of GFP at C-terminus of the PmMOE1 using ribonucleoprotein (RNP) based CRISPR/Cas9 gene editing methodology. The GFP was expressed 18 hours post-transfection, and expression was observed for eight months post-transfection, making it a robust and stable knock-in system.